Generating a structured system of criteria for describing a complicated phenomenon - Ginevičius, Romualdas (Business: Theory and Practice, 2007)
When a phenomenon is getting complicated, acquiring more particular features or aspects, it is becoming more difficult to determine the relationships between the criteria describing it. In this case, it is hardly possible to determine the criteria weights based on expert evaluation. Moreover, the question arises if the statement that the criteria describing a complicated phenomenon are interrelated as the elements of a single system is true. A comprehensive analysis shows that only hierarchically structured system of criteria can adequately describe a complicated phenomenon (CP). This system accounts for the variation of the criteria relationships, when the number of parameters of the phenomenon is growing. The direct relationship can be observed only between the criteria of the same set describing a particular CP aspect, while indirect relationship can be found between the criteria describing various CP aspects. This implies that there is a connection characterized by direct relationship between the aggregated magnitudes pertaining to the criteria considered. The paper offers a method of structuring a system of CP criteria, allowing us to determine the significance of the criteria based on direct relationship between them. Article in Lithuanian. Sudėtingo reiškinio struktūrizuotos rodiklių sistemos formavimas Santrauka. Augant sudėtingo reiškinio (SR) parametrams vis sunkiau tampa susekti ir įvertinti jį apibendrinančių rodiklių tarpusavio ryšius. Ši aplinkybė apsunkina arba netgi padaro neįmanomą rodiklių svorių nustatymą, pagrįstą ekspertiniais vertinimais. Be to, kyla klausimas, ar teisingas tvirtinimas, jog sudėtingą reiškinį atspindintys rodikliai yra tarpusavyje susiję kaip vienos ir tos pačios sistemos elementai. Išsamesnė analizė rodo, kad SR pavaizduoti galima tik hierarchiškai struktūrizuota rodiklių sistema. Ši sistema paaiškina, kaip, augant nagrinėjamo reiškinio parametrams, keičiasi rodiklių tarpusavio ryšiai: tiesioginė sąveika išlieka, bet tik tarp tų rodiklių, kurie pakliūna į tą pačią jų grupę, apibūdinančią tam tikrą SR aspektą; tarp skirtingus aspektus apibūdinančių rodiklių išlieka netiesioginė priklausomybė, t. y. turime sąveiką, pasireiškiančią per tiesioginę, juos apibūdinančių agreguotų dydžių priklausomybę. Straipsnyje pateikiamas SR rodiklių sistemos struktūrizavimas suteikia galimybę nustatyti jų svarbą, remiantis šių rodiklių tiesiogine tarpusavio sąveika. Reikšminiai žodžiai: sudėtingų reiškinių ir procesų kiekybinis įvertinimas, struktūrizavimas, rodiklių sistemos formavimas.